Barriers to culturally safe care for Indigenous Peoples: a key informant perspective - Wilkinson, Ashley Victoria Mary (My University, 2021)
Health inequity for Indigenous Peoples persists on a global scale, due to the ongoing impacts of colonization. Racism, power dynamics, and health professionals with limited understanding of the historical context and lived realities of Indigenous Peoples are among the many factors which create unsafe spaces in health care environments (Turpel et al., 2020; Browne, 2017; Jacklin et al., 2017; Goodman et al., 2017). These unsafe spaces foster unsafe care which undermines the quality of care that Indigenous Peoples receive, with detrimental outcomes. Cultural safety is a health concept originating in New Zealand (and adopted in many other countries such as Australia and Canada) that emphasizes provider reflexivity, facilitates care that is free from discrimination, racism and prejudice, and empowers Indigenous patients to define the quality of the care they receive. There is a growing body of research which suggests that culturally safe care could have a meaningful impact on health experiences of Indigenous Peoples when embedded into practice (Churchill et al., 2020), and supports the idea of cultural safety being incorporated into healthcare environments (Goodman et al., 2017; Wesche, 2013; Schill & Caxaj, 2019). However, cultural safety has not been widely implemented at an organizational or systemic level within the health sector, and remains absent from health policy, despite calls for its implementation (Truth and Reconciliation Commission, 2015). [...]
Keywords: Health inequity; Cultural safety (health care); Indigenous health equity; Culturally safe care for Indigenous peoples